Differentiation and Molecular Properties of Mesenchymal Stem Cells Derived from Murine Induced Pluripotent Stem Cells Derived on Gelatin or Collagen - Chizuka Obara; Kazuya Takizawa; Kenichi Tomiyama; Masaharu Hazawa; Ai Saotome-Nakamura; Takaya Gotoh; Takeshi Yasuda; Katsushi Tajima (Stem Cells International)
The generation of induced-pluripotential stem cells- (iPSCs-) derived mesenchymal stem cells (iMSCs) is an attractive and promising approach for preparing large, uniform batches of applicable MSCs that can serve as an alternative cell source of primary MSCs. Appropriate culture surfaces may influence their growth and differentiation potentials during iMSC derivation. The present study compared molecular properties and differentiation potential of derived mouse iPS-MSCs by deriving on gelatin or collagen-coated surfaces. The cells were derived by a one-step method and expressed CD73 and CD90, but CD105 was downregulated in iMSCs cultured only on gelatin-coated plates with increasing numbers of passages. A pairwise scatter analysis revealed similar expression of MSC-specific genes in iMSCs derived on gelatin and on collagen surfaces as well as in primary mouse bone marrow MSCs. Deriving iMSCs on gelatin and collagen dictated their osteogenic and adipose differentiation potentials, respectively. Derived iMSCs on gelatin upregulated Bmp2 and Lif prior to induction of osteogenic or adipose differentiation, while PPARγ was upregulated by deriving on collagen. Our results suggest that extracellular matrix components such as gelatin biases generated iMSC differentiation potential towards adipose or bone tissue in their derivation process via up- or downregulation of these master genes.